A Preliminary Survey on the Oral Manifestation of COVID-19 in the First and Second Waves in Bhubaneswar, City of Odisha, India - Bhuyan, Ruchi; Bhuyan, Sanat Kumar; Mohanty, Jatindra Nath; Panda, Nihar Ranjan; Bhuyan, Varsha; Ojha, Priyadarshini; Priyadarshini, Pallavi; Sahoo, Gangadhar (National Journal of Community Medicine, 2022)
Background: In both waves of COVID-19 infections, loss of taste was noted in a disproportionately high number of individuals. However, there is a considerable risk of dental disease during and after COVID -19 infections. Aim: Our aim here is to study the oral manifestation of the COVID -19 infections and make a comparison of the severity of presentation in the second wave with the first wave among the general population in Bhubaneswar, city of Odisha, India. Methods: A detailed online questionnaire was developed focusing on the oral manifestation during both the waves using Google forms. Results: Out of a total of 380 RT PCR positive cases, 91/169 and 167/211 cases with oral manifestation were obtained in the first and second waves, respectively. We found 41 (24.26 %) in the first wave and 63 (29.85 %) in the second wave of patients with oral manifestations over the age of 50. Patients receiving oxygen or using a ventilator were found to be 15 (8.9 %) in the first wave and 59 (28%) in the second wave. Conclusion: This is the first study to evaluate the correlation of oral infection with COVID 19 in different waves. This difference could be correlated with the virulence of viruses with mutated strains.